ISOLATION OF ACTINOMYCIN D FROM MARINE DERIVED Streptomyces - Abdullah Rasyid; Kyoko Adachi (Universitas Gadjah Mada, 2007)
The bioactive substance producing strain, a marine bacterium A5S-46 was found in the antibacterial screening. This strain was isolated from the artificial sponge set in the coastal seawater at Iriomote islands (Japan). The crude extract from culture broth of the strain A5S-46 was assayed to the antibacterial activity test against the seven kinds of bacterial test strains. The active substance accumulated in the both bacterial cells and culture supernatant. Based on the 1H NMR and the LC/PDA/MS data, the bioactive substance was identified to be actinomycin D.